Ferroptosis: A New Development Trend in Periodontitis - Kexiao Chen; Shuyuan Ma; Jianwen Deng; Xinrong Jiang; Fengyu Ma; Zejian Li (Cells, 2022)
Periodontitis is a chronic inflammatory disease associated with bacterial biofilm. It is characterized by loss of periodontal support tissue and has long been considered as a “silent disease”. Because it is difficult to prevent and has a health impact that can not be ignored, researchers have been focusing on a mechanism-based treatment model. Ferroptosis is an iron-dependent regulatory form of cell death, that directly or indirectly affects glutathione peroxidase through different signaling pathways, resulting in a decrease in cell antioxidant capacity, accumulation of reactive oxygen species and lipid peroxidation, which cause oxidative cell death and tissue damage. Recently, some studies have proven that iron overload, oxidative stress, and lipid peroxidation exist in the process of periodontitis. Based on this, this article reviews the relationship between periodontitis and ferroptosis, in order to provide a theoretical reference for future research on the prevention and treatment of periodontal disease.